Analysis of Risk Factors for The Incidence of Low Birth Weight Infants at Delia Langkat General Hospital in 2019 - Devi Aprianti; Tri Niswati Utami; Nur Aini (Science Publication: Journal of Public Health and Nutrition, 2025)
According to the statistics collected, 157 babies were born with low birth weight (LBW) in 2016. 142 infants were born with LBW in 2017. 134 infants were born with LBW in 2018. The researcher at Delia Langkat General Hospital found that during the previous three years, the monthly prevalence of LBW cases stayed high. Analyzing the risk variables linked to the prevalence of low birth weight at Delia Langkat General Hospital in 2019 is the aim of this study. This study uses a quantitative research design and a retrospective methodology. The Delia Langkat General Hospital served as the study's site. 138 people made up the study population, and 138 respondents were selected from the sample using a total sampling technique. At a 95% confidence level (α = 0.05), the data were examined using univariate analysis, bivariate analysis using the chi-square test, and multivariate analysis using multiple logistic regression. The findings indicated that a history of preterm birth (p = 0.017 < 0.05) and multiple pregnancies (p = 0.026 < 0.05) were the factors linked to the incidence of LBW at Delia Langkat General Hospital in 2018. Maternal age (p = 0.847 > 0.05), preeclampsia/eclampsia (p = 1.000 > 0.05), birth interval (p = 0.0322 < 0.05), and early rupture of membranes (p = 0.439 > 0.05) were among the variables that were not linked to the risk of LBW. The history of preterm delivery was the most significant factor linked to the incidence of LBW. According to the study's findings, a history of preterm delivery and repeated pregnancies both have an impact on the occurrence of LBW. A history of preterm birth is the most important factor. In order to enhance the delivery of health education on the prevention and risk factors of LBW incidence, it is anticipated that these findings will be able to be used as an assessment reference by healthcare professionals, especially in LBW services. Keywords: Maternal Age, Preeclampsia/Eclampsia, Birth Interval, Multiple Pregnancy, History of Preterm Birth, Premature Rupture of Membranes, Low Birth Weight Incidence